Maqashid Sharia-Based Pesantren Development Index - Solihat, Mutiara; Basir, Dini Putri; Mubarokah, Anisah; Raisa (Maqasid al-Shariah Review, 2023)
This paper discusses the concept of Pondok Pesantren in terms of its etymology and history, describes its role in Islamic education, and explores the concept of Maqashid al-Syariah as the main objective of sharia law. This concept is applied in the context of Islamic boarding schools with a focus on environmental protection as the main variable. This study uses Simple Additive Weighting (SAW) method to assess the achievement of Maqashid al-Syariah in two Islamic boarding schools, namely Pesantren Miftahul Huda Bogor and Pesantren Hidayatullah Balikpapan. The results of the analysis show that both pesantren have good achievements in protecting religion, soul, mind, offspring, and property, but there are differences in environmental indicators. Pesantren Hidayatullah Balikpapan shows better performance in the environmental aspect, making it close to the full achievement of Maqashid Syariah, while Pesantren Miftahul Huda Bogor has some shortcomings in the health and environmental aspects. This study provides a comprehensive picture of the implementation of Maqashid Syariah in pesantren and provides insights into the role of pesantren in Islamic education and the environment.